An introduction to optical burst switching. - Battestilli, T.
Optical burst switching is a promising solution for all-optical WDM networks. It combines the benefits of optical packet switching and wavelength routing while taking into account the limitations of the current all-optical technology. In OBS, the user data is collected at the edge of the network, sorted based on a destination address, and grouped into variable sized bursts. Prior to transmitting a burst, a control packet is created and immediately sent toward the destination in order to set up a bufferless optical path for its corresponding burst. After an offset delay time, the data burst itself is transmitted without waiting for a positive acknowledgment from the destination node. The OBS framework has been widely studied in the past few years because it achieves high traffic throughput and high resource utilization. However, despite the OBS trademarks such as dynamic connection setup or strong separation between data and control, there are many differences in the published OBS architectures. In this article we summarize in a systematic way the main OBS design parameters and the solutions that have been proposed in the open literature.
Keywords: Optical burst switching; All-optical WDM networks; Bufferless optical path; Control packet; Design parameters; Destination node; Offset delay time; Optical packet switching; Resource utilization; Traffic throughput; Wavelength routing